Down the Mysterly River - Willingham, Bill.; Buckingham, Mark (New York : Tom Doherty, 2011)
Top-notch boy scout Max "the Wolf" cannot remember how he came to be in a strange forest, but soon he and three talking animals are on the run from the Blue Cutters, hunters who will alter the foursome's very essence if they can catch them.
"A Starscape Book."
Map on lining papers.
Keywords: Fantasy -- Juvenile fiction; Human-animal communication -- Juvenile fiction; Animals -- Juvenile fiction; Scouting (Youth activity) -- Juvenile fiction; Memory -- Juvenile fiction; Forests and forestry -- Juvenile fiction